2012
DOI: 10.15288/jsad.2012.73.290
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Alcohol Use and Consequences Among Empirically Derived Sexual Minority Subgroups

Abstract: ABSTRACT. Objective: The current study develops an empirically determined classifi cation of sexual orientation developmental patterns based on participants' annual reports of self-identifi cations, sexual attractions, and sexual behaviors during the fi rst 4 years of college. A secondary aim of the current work was to examine trajectories of alcohol involvement among identifi ed subgroups. Method: Data were drawn from a subsample of a longitudinal study of incoming fi rst-time college students at a large, pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 63 publications
(103 reference statements)
4
53
0
Order By: Relevance
“…Within this context, substance use may be integral to promoting social connectedness as part of a younger "lesbian and gay scene" that is often centered in clubs and bars (Valentine and Skelton, 2003) and "sexualized social contexts" such as sex clubs (Garofalo et al, 2007). In that regard, a recent study found that alcohol use among lesbian/bisexual college students, compared with heterosexual women, was more strongly infl uenced by desires to get in with a preferred group, although this same effect was not present among men (Talley et al, 2012). It is also possible that tolerant substance use norms are simply part of a cluster of more liberal attitudes about a broad range of social issues that are characteristic of this subpopulation (Herek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, substance use may be integral to promoting social connectedness as part of a younger "lesbian and gay scene" that is often centered in clubs and bars (Valentine and Skelton, 2003) and "sexualized social contexts" such as sex clubs (Garofalo et al, 2007). In that regard, a recent study found that alcohol use among lesbian/bisexual college students, compared with heterosexual women, was more strongly infl uenced by desires to get in with a preferred group, although this same effect was not present among men (Talley et al, 2012). It is also possible that tolerant substance use norms are simply part of a cluster of more liberal attitudes about a broad range of social issues that are characteristic of this subpopulation (Herek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings concerning sexual-orientation drinking disparities among college students are inconsistent (Eisenberg and Wechsler, 2003; Hatzenbuehler et al, 2008; Kerr et al, 2014; McCabe et al, 2003, 2005; Reed et al, 2010; Ridner et al, 2006; Schauer et al, 2013; Talley et al, 2010, 2012). We know even less about whether LGB and heterosexual students drink in similar or different contexts (e.g., bars, Greek parties, off-campus parties).…”
Section: Introductionmentioning
confidence: 99%
“…sexual minority adolescents) are at increased risk of alcohol problem use compared to their heterosexual counterparts. They are more likely to report earlier onset of alcohol use, more frequent and heavier drinking and more alcohol-related problems [3][4][5][6][7]. A number of studies have found that gender moderated the effect of sexual orientation on drinking, with reports that sexual minority female adolescents are more likely to engage in heavy drinking than males, compared to their heterosexual counterparts [3,8,9].…”
Section: Introductionmentioning
confidence: 99%